HUBUNGAN DUKUNGAN SUAMI DENGAN KUALITAS HIDUP PEREMPUAN MENOPAUSE - Desy Ayu Wardani (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
Background: Menopause phase in women is the time when menstrual cycle stops which is followed by obvious psychological and physical changes and occurs 3 – 4 years. The psychological and physical changes in menopause women will affect the quality of their life. Therefore, supports from the close people, especially from their husbands are needed. Objective: This study aimed to find out the correlation between husband support and the life quality of menopause women. The type of this research was quantitative research using correlation analysis with cross sectional approach with the total of 126 respondents. The technique used in taking the sample was Purposive sampling technique. Chi Square test was used as the bivariate test. Finding: The research finding showed that p-value was 0.032. Conclusion: There was a correlation between husband support and the life quality of menopause women. Suggestion: There should be a follow-up research about the factors which affect the life quality of menopause women such as psychological, physical aspects, social relationship and environment surrounding the menopause women.